Failure of low-level laser therapy to boost healing of venous leg ulcers in surgically and conservatively treated patients - Taradaj, J.; Franek, A.; Cierpka, L.; Krol, P.; Blaszczak, E.; Dolibog, P.; Kusz, D. (Phlebologie, 2008)
Objective: To evaluate in a randomized open-label clinical trial the ability of adjuvant low-level laser therapy (LLLT) to improve healing of venous leg ulcers in surgically and conservatively treated patients. Patients and methods: Eighty three patients with venous leg ulcers were included in this study. Patients in groups 1 and 2 were treated surgically while patients in groups 3 and 4 were treated conservatively. Patients in groups 1 and 3 were additionally treated with the LLLT (GaAlAs laser, 810 nm, 4 J/cm2, 65 mW) once daily, 6 times a week for 7 weeks. Results: After therapy comparison of completely healed wounds, statistically significant differences were seen between groups 1 and 3 (p=0.02), 1 and 4 (p= 0.02), 2 and 3 (p= 0.02), 2 and 4 (p=0.02) in favor of groups 1 and 2. Comparison of the relative change of wound total surface area indicated statistically significant differences between groups 1 and 3 (p=0.002), 1 and 4 (p=0.002), 2 and 3 (p=0.002), 2 and 4 (p=0.002) in favor of groups 1 and 2. Comparison of the other parameters also demonstrated a more efficient therapy effects in groups 1 and 2 than in group 3 and 4. There were no statistical differences in all examined parameters between groups 1 and 2 (p>0.05), 3 and 4 (p>0.05). Conclusion: The application of the LLLT does not enhance healing of venous leg ulcers in surgically and conservatively treated patients. A well conducted surgical operation is much more efficient than conservative pharmacological procedures.
Keywords: LLLT; venous leg ulcers; wound healing